2023
DOI: 10.1007/s11205-023-03167-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Equity in Social Protection Spending on Income Poverty and Inequality

Abstract: This study aims to investigate whether higher equity in government social protection spending strongly predicts positive changes in income poverty and inequality. Our approach was to regress the measures of absolute poverty and inequality on the indicators of equity in social protection spending at the country level, controlling for the level of spending and the country wealth measured by per capita GDP. For that purpose, we have compiled a dataset of 535 observations from 101 countries over years 1998–2017, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Conversely, if economic growth is accompanied by worsening income inequality, poverty may increase rather than decrease. Because of this obvious negative effect of income disparity on poverty reduction, relevant scholars have also conducted a lot of research on the effect of factors such as distribution structure, transfer payments, and fiscal allocation on poverty reduction [13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, if economic growth is accompanied by worsening income inequality, poverty may increase rather than decrease. Because of this obvious negative effect of income disparity on poverty reduction, relevant scholars have also conducted a lot of research on the effect of factors such as distribution structure, transfer payments, and fiscal allocation on poverty reduction [13][14][15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Likewise with infrastructure services, [8] revealed that government spending in the infrastructure sector will accelerate the flow of goods and services and reduce production costs and make it easier for people to access services to other economic sectors and this has an impact on reducing poverty levels. [9] states that social protection spending has an impact on reducing poverty, especially in low-and middle-income countries. This finding is also supported by research from [10]; [11] and [12] which depict that government spending on the social protection sector directly improves the quality of life of the poor.…”
Section: Introductionmentioning
confidence: 99%